Análise e teste de um conversor A/D integrador com faixa de entrada e resolução programável a capacitores chaveados - Pereira, Vinicius Matheus Batista (Brasil, 2022)
Analog-to-digital converters allow digital systems to access the physical analog variables present in the world, but to ensure the quality of the data provided it is necessary to know the performance parameters of the converter. In this course conclusion work, a test circuit for an analog-to-digital converter with input range and programmable resolution using a switched capacitor is developed. The converter was designed at the transistor level and manufactured using AMS 0.35 µ CMOS technology, but its operation and performance still need to be tested experimentally. Its method of operation is studied for application of tests with ramp and sinusoidal signals, through a digital-analog converter and a board with ARM microcontroller. From the results obtained, the static and dynamic parameters of the converter are extracted for a resolution range of 5 and 8 bits, with unity gain and 1.5 times. At the end of the tests, it was possible to validate the performance of the converter for the full 5-bit range, with satisfactory results, however improvements need to be made in the testing methodology for the 8-bit resolution.